On the Evolution and Function of Plasmodium vivax Reticulocyte Binding Surface Antigen (pvrbsa) - Camargo-Ayala, Paola Andrea; Garzón-Ospina, Diego; Moreno-Pérez, Darwin Andrés; Ricaurte-Contreras, Laura Alejandra; Noya, Oscar; Patarroyo, Manuel A. (Frontiers in Genetics, 2018)
The RBSA protein is encoded by a gene described in Plasmodium species having tropism for reticulocytes. Since this protein is antigenic in natural infections and can bind to target cells, it has been proposed as a potential candidate for an anti-P. vivax vaccine. However, genetic diversity (a challenge which must be overcome for ensuring fully-effective vaccine design) has not been described at this locus. Likewise, the minimum regions mediating specific parasite-host interaction have not been determined. This is why the rbsa gene’s evolutionary history is being here described, as well as the P. vivax rbsa (pvrbsa) genetic diversity and the specific regions mediating parasite adhesion to reticulocytes. Paralogues in parasite species invading normocytes, such as P. inui and P. fragile, were found in an exhaustive search, so it seems that the rbsa gene, rather than being exclusive of Plasmodium parasites invading reticulocytes, has been lost in some parasite species belonging to the monkey-malaria clade. The pvrbsa locus had less diversity than other merozoite surface proteins where natural selection and recombination were the main evolutionary forces involved in causing the observed polymorphism. The recombinant PvRBSA-A protein, towards the N-terminal end, bound to reticulocytes having a Duffy-positive phenotype whilst the recombinant PvRBSA-B did not. Interestingly, two PvRBSA-A-derived peptides were able to inhibit protein binding to reticulocytes. The C-terminal region (PvRBSA-B, the most diverse one) is likely involved in immune evasion whilst PvRBSA-A is involved in parasite-host interaction. Specific conserved and functionally important peptides within PvRBSA-A could be considered when designing a fully-effective vaccine against P. vivax.